Branchial cysts - Thomaidis, Vasilios (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Objective. Cysts presented in the lateral aspect of the neck are relatively uncommon anomalies. Many theories have been proposed to explain the aetiology of these cysts, grouped in two main categories: the congenital and the cervical lymph nodes cystic transformation hypotheses. Settings. In this paperwe present 4 patient-cases documented in the department of Maxillofacial Surgery, and try to trace the profile of these lesions and investigate their origin. Results. All lesions were well circumscribed by Computed Tomography, and prior to surgery they were assessed by means of fine needle aspiration cytology. Neutrophils, debris and mature squamous epithelial cells including degenerate forms, were the key-features in the cytological diagnosis. Histologic examination of the excised surgical specimen established the diagnosis in all cases. Conclusions. Our findings, compatible with the congenital theory lead us to the conclusion that the branchial cysts are the result of imperfect obliteration of the branchial clefts, arches, and pouches.
Keywords: Brahiom; Branchioma; ciste; Diagnosis; Glava in vrat, novotvorbe; Head And Neck Neoplasms; novotvorbe; Pathology; rak (medicina); Surgery; Tomografija radiografska, računalniška; Tomography, X-Ray Computed; tumor; vrat; Vrata